Interferometric Method for Determination of X–ray Train Length - Drmeyan, H. R.; Mkhitaryan, S. A.
It is elaborated, made and tested a special interferometer–train metering device. А method for interferometric determination of X–Ray train length is offered. It is proved that the interference pattern disappears, when the path difference between imposing waves is more than the monochromatic X–Ray train length. The limit of disappearance of interference pattern depending on the value of path difference is determined. The X–Ray train length is determined which is close to the meaning determined theoretically.
Keywords: Physics